Managing Successful Change Efforts in the Public Sector: An Employee's Readiness for Change Perspective. (September 2019) - Hameed, Imran; Khan, Abdul Karim; Sabharwal, Meghna; Arain, Ghulam Ali; Hameed, Irfan
This study brings together public and private sector research on change management to highlight the important role of public servants as recipients of change, which is underemphasized in the public management literature. In doing so, we identify and operationalize factors of managing successful change—involved communication and change recipients' beliefs. The effect of involved communication on developing employees' readiness for change is explored. Data were collected from public sector research and development organizations in Pakistan. The results of the structural equation modeling support the positive role of involved communication in developing employees' readiness for change. Employees' organizational identification and change recipients' beliefs also exhibit a significant mediating role in the above-stated relationship. This study significantly contributes to the existing literature of change management in the public sector by focusing on employees as key players in an organization's change process. Practical implications and future research directions are also discussed.